The Role of Customer Trust in Mediating Brand Image, Price, and Product Quality on Customer Loyalty on Beauty Product Customers - Putri Lutfiana S; Nurul Qomariah; Feti Fatimah (Majapahit Journal of Islamic Finance and Management, 2026)
The global beauty industry is experiencing continuous growth as public awareness of self-care, skin health, and personal identity expression increases. This study aims to examine and analyze the influence of brand image, price, and product quality on customer trust and loyalty, as well as to examine and analyze the mediating role of customer trust in the relationship between brand image, price, product quality, and customer loyalty for beauty products in Jember Regency. The respondents in this study were 200 users of local beauty products in Jember Regency. The data source was a questionnaire distributed using proportional stratified random sampling. The data analysis technique used was Partial Least Squares (PLS) processed with SmartPLS software.The results of the study indicate that: 1) the influence of brand image on customer trust has a positive and significant influence on customer trust, 2) the influence of price on customer trust has a positive and significant influence on customer trust, 3) the influence of product quality on customer trust has a positive and significant influence on customer trust, 4) the influence of brand image on customer loyalty is not significant on customer loyalty, 5) the influence of price on customer loyalty has a significant influence on customer loyalty, 6) the influence of product quality on customer loyalty is not significant on loyalty, 7) the influence of customer trust on customer loyalty has a significant influence on loyalty, 8) Customer trust as a mediator between brand image and customer loyalty is proven to have a positive and significant indirect influence, 9) Customer trust as a mediator between price and customer loyalty has a positive and significant indirect influence, 10) Customer trust as a mediator between product quality and customer loyalty has a positive but insignificant indirect influence.